Capturing the inflammatory landscape within kidney compartments of human diabetic kidney disease: a digital spatial profiling study - Elhusseiny, Khaled M.; Deceus, Farha G.; Cornell, Lynn D.; Bian, Xiaohui; Ma, Yaohua; Kachergus, Jennifer M.; Thompson, E. Aubrey; Hickson, LaTonya J. (Frontiers in Endocrinology, 2026)
ObjectiveTo quantitatively examine immune cell markers and spatial distribution in human diabetic kidney disease (DKD) to enhance understanding of the inflammatory landscape contributing to injury. Maladaptive inflammation is an underrecognized contributor to DKD pathogenesis and progression and remains undertreated.Patients and methodsNanoString GeoMx™ Digital Spatial Profiling technology targeted antibodies labeled with unique oligonucleotide barcode in kidney biopsy [DKD (n=5), tubulointerstitial nephritis (TIN; n=4), and normal (n=2)] with regions of interest selection of compartments (glomeruli, tubules, interstitium). Inflammation-related proteins were analyzed with differential expression through linear mixed modeling.ResultsCompared to normal tissue, inflammatory cell surface protein markers were increased in DKD tubules and interstitium. Markers of T cells (CD4, CD44), macrophages (CD68; proinflammatory), and antigen-presenting cells (APCs; CD40 and CD11c) were increased across all DKD compartments (vs. normal). Macrophage (CD163; prorepair) marker was increased in DKD tubules and interstitium (vs. normal). Fewer differences were observed in glomeruli for normal vs. DKD or TIN vs. DKD groups. CD66b+ (granulocytes) cell marker was higher in DKD (vs. TIN). As expected, TIN had higher levels of T cell and macrophage markers in tubules and interstitium (vs. DKD). Interestingly, CD34, a hematopoietic stem cell and endothelial cell marker, was lower in DKD tubules and interstitium (vs. normal) but higher in DKD (vs. TIN).ConclusionNanoString GeoMx DSP technology may fulfil a role in enhancing the understanding the inflammatory landscape engaged in DKD pathogenesis as well as measuring response to therapy. Moreover, additional investigations of CD34 progenitor cell depletion in DKD may be warranted.